Creativity assessment system / Ling Loo Yee - Ling, Loo Yee (2006)
Creativity is an important cognitive construct much sought after in both the education and work environment. Currently, creativity has been given much emphasized in education and both teachers and students are given the necessary training and support by the Education Ministry to enhance this potential. However, creativity assessment has always posed a big challenge. Most valid and reliable creativity tests have been very difficult to score. The laborious scoring procedure has driven researchers and educators to use less reliable and valid measures To overcome this problem, a computer program called the Creativity Assessment System (CAS) was developed to help researchers and educators as well as employers and recruiters to score responses of their students or employees easily. CAS is a system use to assess the creativity level of user which based on three main dimensions, namely Fluency, Flexibility and Originality. This system was designed as a total package whereby it not only gives a valid and reliable score, but also give immediate interpretation of the respondents' scores as well as recommendations on how they will be able to enhance their level of creativity.